2016
DOI: 10.1186/s12889-016-3499-6
|View full text |Cite
|
Sign up to set email alerts
|

Household, psychosocial, and individual-level factors associated with fruit, vegetable, and fiber intake among low-income urban African American youth

Abstract: BackgroundChildhood obesity, one of the greatest challenges to public health, disproportionately affects low-income urban minority populations. Fruits and vegetables (FV) are nutrient dense foods that may be inversely associated with excessive weight gain. We aimed to identify the individual characteristic, psychosocial, and household factors influencing FV and fiber consumption in low-income African-American (AA) youth in Baltimore, MD.MethodsCross-sectional analysis of data collected from 285 low-income AA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…Research has shown that repeated exposure to a specific food increases acceptance (Fildes, van Jaarsveld, Wardle, & Cooke, 2014;Gibson & Cooke, 2017;Turrell, 1998) and exposure to a wide variety of foods in infancy has been linked with greater dietary variety and reduced neophobia in childhood (Mallan, Fildes, Magarey, & Daniels, 2016). Children from more deprived backgrounds tend to be offered fewer fruits and vegetables (Trude et al, 2016), potentially reducing their opportunities for exposure and leading to narrower food preferences compared to children from more affluent households (Turrell, 1998). In this context, the finding of reduced food fussiness in children from lower SES backgrounds might seem counterintuitive.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that repeated exposure to a specific food increases acceptance (Fildes, van Jaarsveld, Wardle, & Cooke, 2014;Gibson & Cooke, 2017;Turrell, 1998) and exposure to a wide variety of foods in infancy has been linked with greater dietary variety and reduced neophobia in childhood (Mallan, Fildes, Magarey, & Daniels, 2016). Children from more deprived backgrounds tend to be offered fewer fruits and vegetables (Trude et al, 2016), potentially reducing their opportunities for exposure and leading to narrower food preferences compared to children from more affluent households (Turrell, 1998). In this context, the finding of reduced food fussiness in children from lower SES backgrounds might seem counterintuitive.…”
Section: Discussionmentioning
confidence: 99%
“…However, high-income countries are more aware of the need to increase fiber intake in order to improve health. In these countries, a large variety of cheap and easy to eat fiber-enriched food, much appreciated by young adults, is available (snacks, bran breakfast cereals) [ 36 , 92 ]. This fact could clearly contribute to enhanced fiber intake.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on community intervention will help to address the widespread obesity and CVD epidemic in Mississippi and empower communities to build capacity to tackle the health disparity dilemmas that exist. These results will inform and shape an effective intervention program for improving dietary intakes [ 6 ]. Dissemination of information among community members about eating practices, and encouraging community members to be actively engaged in discussing and developing solutions within the local socio- structural contexts would also be an important step in addressing chronic disease risk reduction [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity has also become a major challenge to public health. Its high prevalence disproportionately affects low-income urban minority populations [ 6 ]. There is urgent need to increase community knowledge about risk factors for chronic diseases.…”
Section: Introductionmentioning
confidence: 99%